SUPERVISION ON BY-LAW OF LOCAL GOVERNMENT IN INDONESIA: LESSON FROM REFRESHED CENTRAL-LOCAL RELATIONSHIP IN NEW ZEALAND - Junaenah, Inna (DiH: Jurnal Ilmu Hukum, 2020)
AbstractA by-law as a product of local government is valuable as a legal instrument in implementing the duty to regulate and to administer local affairs. Contemporary, the regulation regarding supervision on by-law points a dynamic and controversial respond. The indication has appeared since the competence of the central government to nullify by-law is repealed through the Constitutional Court Verdict. Government reaction on this Verdict indicates a disharmony, due to some ventures to control local government forwards to tight, for which several other legal instruments are issued. This study aims to find a developed notion of supervision on a by-law to enhance the purpose of devolution. In doing so, a lesson learned from New Zealand will be taken into account following the gap found in the legal position of Indonesia. The research finding shows that a trend of regulation on supervision in New Zealand reflects a transitional relationship between central government from hierarchical to a partnership, through empowerment. In contrast, the legal position in Indonesia addresses to a discouragement or distrust mindset. For this reason, the what can fulfil the gap as a lesson learned from New Zealand is by emerging a unique consultative process to the public both in by-law making, repealing, amending, and or reviewing.Keywords: comparative; local government; supervisionAbstrakAnggaran rumah tangga sebagai produk pemerintah daerah berharga sebagai instrumen hukum dalam melaksanakan tugas untuk mengatur dan mengelola urusan lokal. Kontemporer, peraturan tentang pengawasan oleh-hukum menunjukkan respons yang dinamis dan kontroversial. Indikasi ini muncul sejak kompetensi pemerintah pusat untuk membatalkan anggaran rumah tangga dicabut melalui Putusan Mahkamah Konstitusi. Reaksi pemerintah atas Putusan ini menunjukkan ketidakharmonisan, karena beberapa usaha untuk mengen-dalikan pemerintah daerah ke depan dengan ketat, yang mana beberapa instrumen hukum lainnya dikeluarkan. Penelitian ini bertujuan untuk menemukan gagasan yang dikembangkan tentang pengawasan terhadap anggaran rumah tangga untuk meningkatkan tujuan devolusi. Dengan melakukan hal tersebut, pelajaran yang dipetik dari Selandia Baru akan diperhitungkan menyusul kesenjangan yang ditemukan dalam posisi hukum Indonesia. Temuan penelitian menunjukkan bahwa tren regulasi tentang pengawasan di Selandia Baru mencerminkan hubungan transisi antara pemerintah pusat dari hirarki ke kemitraan, melalui pemberdayaan. Sebaliknya, posisi hukum di Indonesia mengarah pada keputusasaan atau pola pikir ketidakpercayaan. Untuk alasan ini, apa yang dapat memenuhi kesenjangan sebagai pelajaran yang dipetik dari Selandia Baru adalah dengan memunculkan proses konsultatif yang unik kepada publik baik dalam pembuatan by-law, pencabutan, amandemen, dan atau peninjauan.Kata kunci: komparatif; pemerintah lokal; pengawasan